New cycloartane triterpene glycosides from Thalictrum ramosum. (March 2016) - Meng, Fan-Cheng; Yuan, Cen; Huang, Xiao-Jun; Wang, Wen-Jing; Lin, Li-Gen; Zhang, Xian-Tao; Jiao, Hao-Yan; Zhang, Qing-Wen
Graphical abstract: Highlights: Three new cycloartane triterpene glycosides were isolated from Thalictrum ramosum. The structures were elucidated by HRESIMS, 1D and 2D NMR. The steric configuration was deduced from ROESY and hydrolysis. Abstract: Three new cycloartane triterpene glycosides, cycloramosides A–C (1 –3 ), were isolated from Thalictrum ramosum B. Boivin. Those compounds were determined as 3- O -α-l -arabinopyranosyl-3β, 16β, 24 S, 25, 30-pentaolcycloartane-16- O -β-d -glucopyranoside (1 ), 3- O -α-l -arabinopyranosyl-3β, 16β, 24 S, 25, 30-pentaolcycloartane-24- O -β-d -glucopyranoside (2 ) and 3- O -α-l -arabinopyranosyl-3β, 16β, 24 S, 25-tetrahydoxylcycloartane-16- O -β-d -glucopyranoside (3 ), respectively. Their structures were elucidated by hydrolysis and extensive spectroscopic methods including 1D and 2D NMR experiments ( 1 H, 13 C, DEPT, COSY, ROESY, HSQC, HMBC) along with HR-ESI–MS analyses.